أخلاقيات الوظيفة وعلاقتها بفاعلية إدارة الصراع التنظيمي: دراسة ميدانية على ديوان بلدية بنغازي - بشير محمد العبار , (Scientific Journal of University of Benghazi, 2019)
The current study aims to determine the work ethics and their dimensions (compliance with rules and regulations, time respect, confidentiality, pairing responsibility, cooperation, courtesy and well behaviour, fairness, transparency and integrity) and its relationship with management of organizational conflict in Benghazi municipality council. For the study purpose, "case study" and descriptive analysis was used. A questionnaire was also used as a tool of collecting the basic data. The study population consisted of all managers of middle, top, and low management (54 managers) in Benghazi municipality council. The results revealed that the level of work ethics and the effectiveness of organizational conflict management were high. There was also a direct and significant correlation between time respect and bearing responsibility dimensions and organizational conflict management. In addition, the study also provided some recommendations that might contribute to enhancement of work ethics role and increase the effectiveness of the organizational conflict management at Benghazi municipality council.